The Usefulness of Three-Dimensional Transesophageal Echocardiography for a Primum Atrial Septal Defect. (November 2015) - Kuroda, Masataka; Kumakura, Minami; Sato, Tomonobu; Saito, Shigeru
Abstract : Supplemental Digital Content is available in the text.